IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN PENDIDIKAN NASIONAL PADA PENYELENGGARAAN PENDIDIKAN TENAGA KESEHATAN PROGRAM D-III KEPERAWATAN DI PROPINSI DKI JAKARTA - ROSA, ELSYE MARIA (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to analyze the implementation of national education policy in the nursing education D-III program in Jakarta Province. The evaluation was based on the implementation of the National Education Systems No. 20 year 2003. The research was conducted at the Akademi keperawatan province in Jakarta. It was using policy analysis method. The sample of this research were 7 person of Akademi Keperawatan, Pusdiknakes and Kopertis 3 that was selected randomly. NVIVO version 8 was used to analyze the data collected. The research findings are: (1) most of the nursing educations were Diploma III vocational educations; (2) the ownership status of nursing academies was in the hand of private; (3) the management of diploma III nursing education owned by public was mostly executed by the Department of Health through the Center of Health National Education and Agency for Health of the Jakarta Province; (4) three duty university was not yet implemented completely as a mandatory reference for the institutions and lecturers. Based on these findings, it could be concluded that --- the implementation of National Education Systems No. 20 year 2003 in performing nursing education diploma III was not carried out well. This was happened because of the involving parties were not able to cooperate effectively and efficiently. Transitional management by the Department of Health, in this case the Center of Health National Education and Agency for Health of the Jakarta Province was not implemented thoroughly. Thereby, the implementation of the National Education Law No. 20 year 2003 could be in jeopardy simply because of its inappropriate execution.Key words: National Education Systems No. 20 year 2003, Nursing education D-III Program